O2-6-06. The role of gaze in performing the trail making test. Issue 9 (September 2017) - Terao, Yasuo; Matsuda, Shun-ichi; Tokushige, Shin-ichi; Inomata-Terada, Satomi; Hamada, Masashi; Ugawa, Yoshikazu
Abstract : We studied the role of gaze in performing the trail-making test (TMT) in eight normal subjects, a task frequently used to assess frontal executive function in neurological patients. TMT was presented on a touch-panel monitor placed in front of the subjects, on which they were asked to connect the presented numbers with their fingers in an ascending order (version A), or with the added task of alternately connecting between the numbers and letters in ascending and alphabetical orders (version B), respectively. The subjects' gaze position on the monitor was recorded by a video-based eye tracking system (Eyelink 1000), as was the hand (finger) position on the touch-panel. The completion time and the total number of saccades made during the task, the amplitude, peak velocity of saccades and the interval between consecutive saccades (i.e., fixation duration) were measured. Multiple regression analysis showed that the task completion time correlated with the total number of saccades and, less prominently, with the mean fixation duration, suggesting that gaze plays an important role in performing TMT, and should be considered when using this task to assess executive function in neurological patients with eye movement disorders.